2023
DOI: 10.1161/strokeaha.123.043882
|View full text |Cite
|
Sign up to set email alerts
|

Association of Baseline Cerebrovascular Reactivity and Longitudinal Development of Enlarged Perivascular Spaces in the Basal Ganglia

T.J. Libecap,
Christopher E. Bauer,
Valentinos Zachariou
et al.

Abstract: BACKGROUND: Increasing evidence suggests that enlarged perivascular spaces (ePVS) are associated with cognitive dysfunction in aging. However, the pathogenesis of ePVS remains unknown. Here, we tested the possibility that baseline cerebrovascular dysfunction, as measured by a magnetic resonance imaging measure of cerebrovascular reactivity, contributes to the later development of ePVS. METHODS: Fifty cognitively unimpaired, older adults (31 women; age r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Of the 7 longitudinal studies, 60 , 61 , 64 , 88 , 89 , 90 , 96 only 2 60 , 90 did not find an association between cerebrovascular reactivity and progression of cSVD, with follow‐up times ranging from 1 to 7 years after the initial assessment of cerebrovascular reactivity. These longitudinal studies primarily focused on white matter hyperintensities; for example, Liem et al 61 divided 38 participants into 2 groups by the median cerebrovascular reactivity and reported that in participants with a high cerebrovascular reactivity at baseline, the increase in white matter hyperintensity volume over 7.1 years was 0.37% compared with 2.9% in those with a low cerebrovascular reactivity.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Of the 7 longitudinal studies, 60 , 61 , 64 , 88 , 89 , 90 , 96 only 2 60 , 90 did not find an association between cerebrovascular reactivity and progression of cSVD, with follow‐up times ranging from 1 to 7 years after the initial assessment of cerebrovascular reactivity. These longitudinal studies primarily focused on white matter hyperintensities; for example, Liem et al 61 divided 38 participants into 2 groups by the median cerebrovascular reactivity and reported that in participants with a high cerebrovascular reactivity at baseline, the increase in white matter hyperintensity volume over 7.1 years was 0.37% compared with 2.9% in those with a low cerebrovascular reactivity.…”
Section: Resultsmentioning
confidence: 90%
“…Abstract screening and exclusion of nonoriginal research, records lacking full text, or records that did not quantitatively assess a relationship between cerebrovascular reactivity and cSVD resulted in 46 publications for qualitative synthesis in the systematic review. Of the 46 articles, 3 assessed recent small subcortical infarcts, 51 , 52 , 53 8 assessed the presence of lacunes, 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 7 assessed enlarged perivascular spaces, 52 , 57 , 58 , 59 , 62 , 63 , 64 9 assessed cerebral microbleeds, 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 65 41 assessed white matter hyperintensities, 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%